2020
DOI: 10.1051/e3sconf/202022203020
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility management in apple orchard with microbial biofertilizers

Abstract: Intensification of horticulture in Russia involves planting of new high-density orchards with drip irrigation and fertigation as well as intensification of the exploitation of traditional orchards. This approach involves an increase in mineral fertilizer application imposing the risk of soil fertility loss. For several reasons, the use of traditional organic fertilizers like manure in orchards is currently marginal. Although bacteria-based biofertilizers cannot substitute mineral fertilizers completely, they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, the use of B. mucilaginosus in an apple orchard on chernozem soils did not increase significantly the exchangeable K concentration in the rhizosphere of the trees; on the contrary, it was considerably lower than when mineral K fertilizer was applied [22]. Microbiological biofertilizers significantly affected apple yield only in combination with mineral K fertilizer application, although the latter were applied at a reduced rate [101,102]. Holb et al [103] compared the nutrient uptake among 39 apple cultivars in non-irrigated conventional and organic orchards at soil pH 5.1.…”
Section: The Application Of Microbial Cultures For Soil K Mobilizationmentioning
confidence: 85%
“…However, the use of B. mucilaginosus in an apple orchard on chernozem soils did not increase significantly the exchangeable K concentration in the rhizosphere of the trees; on the contrary, it was considerably lower than when mineral K fertilizer was applied [22]. Microbiological biofertilizers significantly affected apple yield only in combination with mineral K fertilizer application, although the latter were applied at a reduced rate [101,102]. Holb et al [103] compared the nutrient uptake among 39 apple cultivars in non-irrigated conventional and organic orchards at soil pH 5.1.…”
Section: The Application Of Microbial Cultures For Soil K Mobilizationmentioning
confidence: 85%
“…Derkowska et al (2017) have observed that the use of Micosat F, a preparation containing microorganisms, has a beneficial effect on the root system of apple trees. In the cultivation of 'Berkutovskoye' apple trees, Kuzin et al (2020), using half the dose of NPK fertilizers (N 45 P 15 K 60 ) together with a consortium of microorganisms (Azotobacter chroococcum, Bacillus subtilis, B. megaterium, Trichoderma harzianum), obtained an apple yield of the same amount as that obtained with the full NPK dose (N 90 P 30 K 120 ). The positive effect of microorganisms applied together with mineral fertilizers in full and reduced doses has also been noted in other cultivated species (Zafar-ul-Hye et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Table 5, specific examples of the application of PGPB in fruit orchards can be found, for different species. In the case of apples according to Kuzin et al, 2020, fruit yield (kg tr −1 ), was improved when PGPB was applied (12-13%), in comparison with the control (11%) [62]. Thokchom et al, 2014, applied PGPB to citrus plant and evaluated the growth, registering an increase on plant height (40-55 cm) when compared with the control (31 cm) [90].…”
Section: Pseudomonas Bijieensismentioning
confidence: 99%